Mobile Data Usage on Online Learning during COVID-19 Pandemic in Higher Education - Budiman, Edy (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Information about network availability and the amount of internet data usage is very important for planning and implementing management of free internet data assistance programs in the COVID-19 pandemic for students. Research Objectives to analyze for the mobile data usage in online learning (Zoom cloud meetings apps) during the COVID-19 pandemic at Higher Education institutions. The results study revealed that access to online learning using the Zoom cloud meeting apps for 1-minute internet data usage of 5.02bB for a meeting duration of 40 minutes and for a meeting duration of 60 minutes (1 hour) of 13.66 Mb. The measurement results are then used as a reference in the internet data assistance program for students as an effort in supporting the online learning process (Learning-From-Home), objective and proportionate in its distribution to beneficiaries